MARKETING AS AN INVISIBLE COMPONENT OF BUSINESS: STRATEGIES AND CHALLENGES - Bilyk , I. I.; Krykavskyy , V. E. (The actual problems of regional economy development, 2024)
The article discusses the importance of marketing and its role in achieving success for modern enterprises. It emphasizes that the success of enterprises is determined not only by the correct choice of methods for realizing their potential but also by a deep understanding of market opportunities, threats, and prospective changes. An analysis of key theoretical sources and publications by renowned scholars allowed for the systematization and generalization of theoretical knowledge in the fields of marketing and strategic management. Statistical analysis was used for a quantitative assessment of the effectiveness of applying strategies and their impact on the competitiveness of enterprises. By synthesizing information, the role of marketing in the modern business environment and its strategic influence on enterprises were established. This approach made it possible to obtain a comprehensive understanding of the essence and significance of marketing strategies in modern economic practice. The stages of electronic marketing are considered in detail, starting with the preparatory stage, where information is collected about potential customers and their needs, and ending with after-sales service. The importance of using digital technologies in marketing was emphasized, highlighting changes in customer interaction through virtual communication tools. The scientific novelty lies in highlighting current trends in the field of marketing, including artificial intelligence, video advertising, social networks, content for people, and storytelling. These areas define new demands and expectations of consumers, which reflect not only technological progress, but also create new opportunities for business. The importance of contextual advertising was discussed, pointing out its increasing effectiveness, conversion rate, and opportunities for campaign customization. It was noted that the success of electronic marketing requires a comprehensive approach and the use of various tools, from data collection to the creation of attractive content and active customer engagement. The importance of a comprehensive approach to electronic marketing and the use of various tools to attract customers were emphasized. The challenges faced by enterprises in the field of marketing were highlighted, requiring flexibility and constant improvement of strategies for successful operation in the modern competitive environment.